83‐3: Calibration of Colorimeters for RGBW Displays. Issue 1 (29th May 2019) - Bodner, Ben; Robinson, Neil
Abstract : Evidence is presented that the standardized approach to calibrating colorimeters results in large errors when used with multi‐primary displays. A new approach to correct colorimeter measurements for displays with a white sub‐pixel is proposed, reducing error to levels expected with the standard approach on a typical RGB display.